2018
DOI: 10.1177/2333721418778194
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Perceived Social Support and Depressive Symptoms Among Community-Dwelling Older Chinese Americans

Abstract: Purpose: This study examined the association between social support and depressive symptoms among U.S. Chinese older adults. Methods: Data were from the Population Study of Chinese Elderly in Chicago (PINE) study. Independent variables were positive and negative perceived social support (PSS). Dependent variable was depressive symptoms. Multinomial logistic regression analyses were performed. Results: A total of participants were 3,157 Chinese older adults with the mean age of 72.8 years (range 60-105 years). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 40 publications
1
18
1
Order By: Relevance
“…Many theories posits that having low social support is a risk factor for ill health and disease (Barth, Schneider, & von Kane, 2010). In contrast, previous research has shown that social support may buffer the effects of stress and depression in individuals with chronic illness (Chao, Katigbak, Zhang, & Dong, 2018;Liu, Hernandez, Trout, Kleiman, & Bozzay, 2017). Notably, a small number of research has documented the link between social support and improved BP, particularly in African-Americans (Bell, Thorpe, & Laveist, 2010;Coulon & Wilson, 2015).…”
mentioning
confidence: 89%
“…Many theories posits that having low social support is a risk factor for ill health and disease (Barth, Schneider, & von Kane, 2010). In contrast, previous research has shown that social support may buffer the effects of stress and depression in individuals with chronic illness (Chao, Katigbak, Zhang, & Dong, 2018;Liu, Hernandez, Trout, Kleiman, & Bozzay, 2017). Notably, a small number of research has documented the link between social support and improved BP, particularly in African-Americans (Bell, Thorpe, & Laveist, 2010;Coulon & Wilson, 2015).…”
mentioning
confidence: 89%
“…A meta-analysis illustrated that older adults with more social support had lower prevalence of depression [ 25 ]. Lack of social support and feelings of loneliness are believed to be risk factors for depression in the elderly [ 26 , 27 ] and perceived social support has been negatively associated with late-life depressive symptoms [ 28 ]. Also, living alone and decreased social participation and engagement reduce positive emotions of an older individual [ 29 – 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding psychological well-being, the included six articles detail the potential risk factors and impacts of psychological distress among global Chinese populations and challenge our assumptions about how individual and familial factors relate to psychological distress and well-being in immigrant populations. Specifically, different forms of psychological distress may have negative impacts of cognitive function ( Y. Chen, Wang, Liang, Sun, & Dong, 2018 ; Kong, Davitt, & Dong, 2018 ), but psychological distress may be buffered by individual, social, and familial resources for both Chinese in China and in the United States ( Chao, Zhang, & Dong, 2018 ; M. Li & Dong, 2018 ; Liu et al, 2018 ; Wang & Dong, 2018 ). In addition, articles in this issue examine how neighborhood and community may impact minority immigrant older adult populations.…”
Section: Study Findingsmentioning
confidence: 99%
“…Specifically, different forms of psychological distress may have negative impacts of cognitive function (Y. Chen, Wang, Liang, Sun, & Dong, 2018; Kong, Davitt, & Dong, 2018), but psychological distress may be buffered by individual, social, and familial resources for both Chinese in China and in the United States (Chao, Zhang, & Dong, 2018; M. Li & Dong, 2018; Liu et al, 2018; Wang & Dong, 2018).…”
Section: Study Findingsmentioning
confidence: 99%